Exploring the role of bodily experience in spatial thinking during the architectural design process - Alaçam, Sema (ACM, 2014)
Architects substantially develop their ideas in space through a visual apprehension of spatial relations. Bodily experience fundamentally influences architects' way of thinking during the design process in terms of perception of the space, bodily interaction with the physical environment, the mental imagery constructed in ones' mind and recollection of spatial data. We argue that the exploration of gestural and kinesthetic interaction between the designers and their design models provides an enhanced understanding of how traditional design environments provide for facilities intuitive interaction between designers and their design models. As an attempt to understand how the bodily experience influences the development of spatial ideas, we aim to explore the impact of gestural and kinesthetic interactions on designers' spatial thinking during the architectural design process by a case study where we analyze students' presentation of architectural design ideas.